A highly selective and simple spectrophotometric method for the determination of zinc at nano-trace levels in some environmental, biological, food, and pharmaceutical samples using 2-hydroxynaphthaldehydebenzoylhydrazone - Ahmed, Mohammed Jamaluddin; Hossain, Faisal; Mahmood, Esham (European Journal of Chemistry, 2020)
A simple, ultra-sensitive, and highly selective spectrophotometric method has been established for the trace quantification of zinc (Zn), using 2-hydroxynaphthaldehyde benzoylhydrazone (HNABH). Zn forms a pale yellowish-green complex (maximum absorption at 426 nm) with HNABH (1:1, v:v) in a marginally acidic solution (0.00005-0.00023 M H2SO4). The average molar absorption coefficient and Sandell’s sensitivity were found: 2.87×105 L/mol.cm and 12 ng/cm2 of Zn, respectively. The observed linearity range for Zn was 0.01-50 mg/Lwith a detection limit of 1 µg/L. The analysis of biological, food, and vegetable samples using the suggested method were found to be in tremendous accord with those acquired by Atomic Absorption Spectroscopy (AAS) and Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). The method has high precision and accuracy (s = ±0.01 for 0.5 mg/L). The limit of quantification of the proposed method was 10 µg/L.